Molecular mechanisms of antiproliferative and apoptosis activity by 1,5-bis(4-hydroxy-3 methoxyphenyl) 1,4-pentadiene-3-one (ms13) on human non-small cell lung cancer cells - Wan Mohd Tajuddin, Wan Nur Baitty; Abas, Faridah; Othman, Iekhsan; Naidu, Rakesh (MDPI, 2021)
Diarylpentanoid (DAP), an analog that was structurally modified from a naturally occurring curcumin, has shown to enhance anticancer efficacy compared to its parent compound in various cancers. This study aims to determine the cytotoxicity, antiproliferative, and apoptotic activity of diarylpentanoid MS13 on two subtypes of non-small cell lung cancer (NSCLC) cells: squamous cell carcinoma (NCI-H520) and adenocarcinoma (NCI-H23). Gene expression analysis was performed using Nanostring PanCancer Pathways Panel to determine significant signaling pathways and targeted genes in these treated cells. Cytotoxicity screening revealed that MS13 exhibited greater inhibitory effect in NCI-H520 and NCI-H23 cells compared to curcumin. MS13 induced anti-proliferative activity in both cells in a dose- and time-dependent manner. Morphological analysis revealed that a significant number of MS13-treated cells exhibited apoptosis. A significant increase in caspase-3 activity and decrease in Bcl-2 protein concentration was noted in both MS13-treated cells in a time- and dose-dependent manner. A total of 77 and 47 differential expressed genes (DEGs) were regulated in MS13 treated-NCI-H520 and NCI-H23 cells, respectively. Among the DEGs, 22 were mutually expressed in both NCI-H520 and NCI-H23 cells in response to MS13 treatment. The top DEGs modulated by MS13 in NCI-H520—DUSP4, CDKN1A, GADD45G, NGFR, and EPHA2—and NCI-H23 cells—HGF, MET, COL5A2, MCM7, and GNG4—were highly associated with PI3K, cell cycle-apoptosis, and MAPK signaling pathways. In conclusion, MS13 may induce antiproliferation and apoptosis activity in squamous cell carcinoma and adenocarcinoma of NSCLC cells by modulating DEGs associated with PI3K-AKT, cell cycle-apoptosis, and MAPK pathways. Therefore, our present findings could provide an insight into the anticancer activity of MS13 and merits further investigation as a potential anticancer agent for NSCLC cancer therapy